Effects of Initial Powder Size on the Densification of Barium Titanate Ceramics Prepared by Microwave‐Assisted Sintering. Issue 4 (24th January 2015) - Yun, Han‐Sol; Kim, Hyo‐Han; Jeong, Dae‐Yong; Cho, Nam‐Hee; Chan, H.
<x xml:space="preserve">Abstract</x> The effects of initial powder size on microwave‐assisted sintering (MWS) were investigated. BaTiO3 powders with an average particle size of 50, 100, and 500 nm were prepared and sintered with MWS and conventional heating‐based sintering (CS). Samples of the 50 ‐ and 100‐nm‐sized BaTiO3 powders were mechanically milled to study the effects of powder crystallinity on microwave absorption during the MWS process. The MWS of the 50‐nm‐sized BaTiO3 powder resulted in a relative mass density of more than 90% when sintered at 1050°C, whereas the same density was achieved at 1200°C with CS. This difference between the optimal sintering temperatures, which is caused by the absorption of microwaves, was not observed when the 500‐nm‐sized BaTiO3 powder was used. The sinterability of the BaTiO3 ceramics prepared through the MWS of mechanically milled, 50‐nm‐sized powders decreased with increasing milling time. However, the sinterability was much higher than that of the BaTiO3 ceramics prepared through the MWS of the 100‐ and 500‐nm‐sized unmilled powders. In conclusion, microwave absorption has significant effects on the sintering behavior of 50‐nm‐sized powders, but is negligible for 500‐nm‐sized powders.